AC susceptibility and electrical properties of PbS added Bi1.6Pb0.4Sr2CaCu2O8 superconductor - M.J. Masnita,; Rozidawati Awang,; R. Abd-Shukor, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The Bi1.6Pb0.4Sr2CaCu2O8 (Bi-2212) phase is an interesting superconductor. Although it’s transition temperature is lower than Bi1.6Pb0.4Sr2Ca2Cu3O10 (Bi-2223), it has a better high field performance at low temperatures. This report is regarding the effects of lead sulfide on Bi1.6Pb0.4Sr2CaCu2O8 superconductor. Samples of Bi1.6Pb0.4Sr2CaCu2O8(PbS)x for x = 0.0 to 10.0 wt.% were prepared via the solid-state-reaction route. The Bi-2212 was the majority phase in all samples with x ≤ 1.0 wt.% showing more than 95%. Scanning electron micrographs showed increase in grain size as PbS content was increased. The x = 0 sample exhibited the highest Tc-zero at 72 K and Tc-onset 83 K. The imaginary part of the AC susceptibility showed that the peak temperature, Tp increased from 59 K for x = 0 to 66 K for x = 0.6 wt.% sample. This research showed that PbS increased the flux pinning of Bi-2212 for x ≤ 1.0 wt.% although the transition temperature was suppressed.